A comparative study on the relative effectiveness of the whole-part method and the part-whole method of beginning reading in grade one with Filipino as the medium of instruction - Arabit, Priscila Dionisio 1924- (s.n.], 1966)
This is a comparison of the relative effectiveness of the Whole-Part Method and the Part-Whole Method of beginning reading in grade one, with Pilipino as the medium of instruction. The method of teaching beginning reading in Pilipino was also identified. The author believes that the language helps develop better skills in the recognition of words and in comprehension.